Increasing dependency of older people in nursing homes is associated with need for dental treatments - Zenthöfer, Andreas; Rammelsberg, Peter; Cabrera, Tomas; Hassel, Alexander J. (Neuropsychiatric disease and treatment, 2014)
Increasing dependency of older people in nursing homes is associated with need for dental treatments Andreas Zenthöfer, Peter Rammelsberg, Tomas Cabrera, Alexander Jochen Hassel Department of Prosthodontics, Dental School, University of Heidelberg, Heidelberg, Germany Abstract: To determine relationships between the need for dental treatments of institutionalized elderly people and cognitive impairment and the general level of care needed. Two hundred and sixty-eight residents of long-term care facilities in Germany were included in this study. Age, sex, diseases, number of frequently taken drugs, and location of the long-term care facility of the participants were recorded. For each participant, the need for care was assessed by use of the Barthel index (BI). Cognitive impairment was evaluated by use of the mini-mental state examination (MMSE). To assess dental treatment needs, the revised oral assessment guide (ROAG) was applied for different oral health conditions, which were rated “healthy” or “treatment needed”. Spearman correlations were performed to evaluate associations between BI and MMSE and dental treatment needs. Statistical analysis revealed significant associations of BI (P<0.001) and MMSE (P=0.015) with the ROAG score. Increasing dependency and decreasing cognitive ability worsen oral health and increase the need for dental treatment. Keywords: elderly, dependency, Barthel index, treatment needs, oral health
Gesehen am 09.11.2020